1985
DOI: 10.1055/s-2008-1059704
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Tube Oesophagoplasty for Oesophageal Atresia: A Follow-Up Study

Abstract: In 1982 a programme of multi-disciplinary follow-up on 12 patients that underwent a gastric tube oesophagoplasty for long-gap oesophageal atresia was started. Radiological examination, performed on all gastric tubes but one (died a few days after surgery), assessed the morphology and dynamics of gastric tube, either distally or proximally based, and stomach 2 to 8 years after surgery. Endoscopic backward exploration was performed on 7 cases, to allow a closer analysis of stomach, gastric tube mucosa and upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a long-term follow up study of 37 patients with gastric tube perforation, Goon et al demonstrated that reflux up the gastric tube was relatively common, but only a minority were mildly symptomatic and easily managed conservatively. There were no Other studies showed also that the long-term prognosis of gastric tube oesophagoplasties is quite good [3][4][5]. Peptic ulceration of the gastric tube in two patients has been reported by Anderson et al [6].…”
Section: Discussionmentioning
confidence: 95%
“…In a long-term follow up study of 37 patients with gastric tube perforation, Goon et al demonstrated that reflux up the gastric tube was relatively common, but only a minority were mildly symptomatic and easily managed conservatively. There were no Other studies showed also that the long-term prognosis of gastric tube oesophagoplasties is quite good [3][4][5]. Peptic ulceration of the gastric tube in two patients has been reported by Anderson et al [6].…”
Section: Discussionmentioning
confidence: 95%